Design of Complex Multiplier Using Vedic Mathematics - Hassan, Hasliza (International Journal of Integrated Engineering, 2023)
In this project, a 4x4 multiplier is implemented that utilizes the Urdhava Tiryakbhyam sutra method in Vedic mathematics. This method is applicable in all two decimal number multiplications which offers high speed calculation and improved efficiency. Thus, the design of a 4x4 Vedic-based multiplier is solely aimed at performing faster multiplications and achieving quicker processing speeds than the traditional multipliers. The architecture of the Vedic multiplier consists of four 2x2 multipliers and three adders of different bit sizes that are assembled using the Wallace tree implementation. The coding for the multipliers and adders is written in Verilog Hardware Description Language (HDL) in the Quartus Prime 17 Software. Functional simulation is then carried out to ensure that the Vedic multiplier performs the accurate multiplication operations, while the Verilog Compiled Simulator is employed to compile and simulate the multiplier design. Following this, the Design Compiler (DC) and Integrated Circuit Compiler (ICC) command scripts are then composed to allow the logic and physical synthesis to be performed on the Vedic and traditional multipliers. From there, the performance level of both these multipliers are assessed through reference to several key parameters such as timing, area, power consumption, overflow percentage and congestion statistics. Based on the results obtained in the synthesis process, the Vedic multiplier possesses faster operational speed than the traditional multiplier (due to a shorter processing time), but ultimately exhibits a greater power consumption and wider area coverage.